FEATURES OF THE DEVELOPMENT OF OUTSOURCING IN THE AVIATION INDUSTRY - T. Rogulenko (Publishing House of the State University of Management, 2017)
The article discusses one of the widely used in the world practice forms of business organization, called «outsourcing». Identified the economic essence of the concept of «outsourcing», discussed peculiarities of its application and evolution in the domestic aviation industry. The main theoretical and practical approaches to formation of an environment conducive to the development of outsourcing in the aviation industry.